A Prospective Randomized Study of Laparoscopic Cholecystectomy Performed Under Spinal Anesthesia - Pradhan, Tanu Deepak Kumar; Agrawal, SurajKumar K.; Rewale, Venktesh (Journal of Biomedical and Pharmaceutical Research, 2021)
Background: When performing a laparoscopic cholecystectomy, spinal anesthesia has proven to be more affordable than general anesthesia.Aim: The purpose of the study was to compare the effectiveness, safety, and cost-benefit of performing a laparoscopic cholecystectomy under spinal anesthesia (SA) against general anesthesia (GA).Settings And Design: An urban non-teaching hospital carried out a thirteen-month prospective randomized research. Supplies and Procedures: Intraoperative events and postoperative pain scores were the secondary outcome measures, while mean anesthesia time, pneumoperitoneum time, and surgery time defined the primary outcome measure for patients meeting inclusion criteria and randomly assigned to groups A and B, respectively, to receive standard techniques for SA and GA, respectively, during a three-port laparoscopic cholecystectomy. The student t-test, Pearson's chi-square test, and the Fisher exact test were the statistical analyses employed.Results: The analysis of 298 patients—196 instances in group A and 102 cases in group B—showed that the GA group had a slightly longer mean anesthetic time, whereas the SA group had a slightly longer pneumoperitoneum time and, consequently, a slightly longer total operation time. In both groups, there were no reported postoperative complications. At the time of discharge after 24 hours, pain alleviation was comparable in the SA group and much greater in the postoperative period (06 and 12 hours). In neither group were readmissions or late postoperative complications reported.Conclusion: Spinal anesthesia was used during the laparoscopic cholecystectomy procedure since it is a practical and secure regular anesthesia. It is suggested that spinal anesthesia be used as the anesthetic method for laparoscopic cholecystectomy in hospital settings in underdeveloped nations where cost is a primary consideration.